Enseñar programación a niños, jóvenes y adultos usando la plataforma Arduino - Arias-Méndez, Esteban (2017)
Computer programming nowadays is one of the most important skill to learn for the future. Here are some insights about the experience of teaching programming to kids, young and adult people on a different way of the traditional class using a more interactive tool to attract a better attention and interaction about the programming concepts. This is achieve with the use of the Arduino platform. During this process we have applied different tools to test the better way for the students to get the skills in a natural way. We also review some of the problems found about the use of the English language in programming languages for a not native English speaking people. High level programming languages are use to say they are high level because the language ”looks” like natural language; however, for non native English speakers this is not always true, specially when this is applied to kids. We propose then the use of different tools to teach programming, beyond the language of the students.